Psychometric properties of the Chinese version of the body image life disengagement questionnaire in a sample of adolescents - Kun Zhang; Huixing Huang; Qiaosong Wang; Lin Ye; Rongjin Lin (BMC Psychology)
Abstract Background The negative consequences of body image concerns manifest in ways such as negative emotional experiences, eating disorders, and problems with social life. The Body Image Life Disengagement Questionnaire (BILD-Q) is an instrument for assessing the impact of body image concerns specifically on adolescents’ life disengagement. The objective of this study is to create a Chinese version of the BILD-Q and assess its validity and reliability with Chinese adolescents. Methods A total of 593 adolescents were recruited, of whom 316 (Sample 1) completed only the BILD-Q and 277 (Sample 2) completed the BILD-Q, Eating Attitudes Test (EAT), and Body Appreciation Scale-2 (BAS-2). Data from Sample 1 were used for the item analysis, exploratory factor analysis (EFA), and test-retest reliability, while data from Sample 2 were used for the BILD-Q’s confirmatory factor analysis (CFA) and associations of BILD-Q with EAT and BAS-2. Both samples were used together for calculating descriptive statistics, measurement invariance, and internal consistency. EFA and CFA were used to verify the single-factor structure of the BILD-Q. Measurement invariance across genders was verified by multi-group CFA. The reliability of the instrument was verified using Cronbach’s alpha and the intraclass correlation coefficient (ICC). Finally, the convergent validity of the instrument was verified by correlating the BILD-Q scores with the EAT and BAS-2 scores. Results The results support a single-factor structure for the Chinese version of the BILD-Q, with good reliability (Cronbach’s alpha = 0.888, ICC value = 0.759). Gender invariance was established: no significant differences were found in BILD-Q scores between the male and female groups. Life disengagement was positively correlated with eating disorder psychopathology and negatively correlated with body appreciation, supporting the convergent validity of the BILD-Q. Conclusion The Chinese version of the BILD-Q has strong psychometric properties when used with Chinese adolescents and can be used to assess the impact of body image concerns on their life disengagement.